Evaluasi Sistem Proteksi Motor Induksi 3 Fasa sebagai Mesin Bubut di CV. Multi Teknik Perkasa (MTP) - Ahmad Dahlan; M. Saleh Al Amin; Perawati Perawati; Yudi Irwansi (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Cv.Multi Teknik Perkasa (MTP) is an individual company which operates in the field of tools, commonly known as lathes. This company handles repair, cutting and scraping of working media such as iron, steel and others. CV. Multi Teknik Perkasa (MTP) uses a 3 phase induction motor for each production process. One of the lathe driving machines used is a 3 phase 380V induction motor with 6KVA power. This induction motor has a Mini Circuit Breaker (MCB), Contactor, and Thermal Overload Relay (TOR) protection system, which functions as an overload controller so that the electric motor is not easily burned or damaged due to overload. For Mini Circuit Breaker (MCB), which in accordance with the standards of the National Electrical Manufactures Association (NEMA). According to research results, the correct size is 25 A while the installed one is 20 A, which of course is not appropriate. For contactors, which are installed at 65 A while the analysis results are 12 A, the three-phase induction motor protection system must be updated or improved. Previously using DiazedFuse (fuse), replaced with a contactor with a current setting of 12 A, so that the motor can avoid being damaged or burned due to the load. Moreover, to find out the power requirements of the induction motor to carry out the turning process, you need the tools to do it, including amper pliers, thermogun, tachometer, so the motor power for turning without load is 5.5A while with a 0.5mm tire the motor power increases to 6A and the maximum load limit is 1mm turning motor power 12A.